Criminal evidence - Ingram, Jefferson; Klotterm, John. (Waltham, Mass. Anderson, 2012)
"A textbook for individuals teaching or learning about the evidentiary framework in the administration of criminal justice. The materials presented cover general evidence law in use by the states and the federal justice system"-- Provided by publisher.
Machine generated contents note: History and Approach to Study 1. History and Development of Rules of Evidence 2. Approach to the Study of Criminal Evidence Proof by Evidence and Substitutes 3. Burden of Proof 4. Proof via Evidence 5. Judicial Notice 6. Presumptions, Inferences, and Stipulations General Admissibility Tests 7. Relevancy and Materiality 8. Competency of Evidence and Witnesses Evidence Via Witness Testimony 9. Examination of Witnesses 10. Privileges 11. Opinions and Expert Testimony 12. Hearsay Rule and Exceptions Evidence Via Documents and Real Evidence 13. Documentary Evidence 14. Real Evidence 15. Results of Examinations and Tests Exclusion of Evidence on Constitutional Grounds 16. Evidence Unconstitutionally Obtained Part II: Judicial Decision Relating to Part I Glossary Appendix I: Federal Rules of Evidence for United States Courts and Magistrates Appendix II: Table of Jurisdictions in which Uniform Rules of Evidence have been Adopted 2009 Appendix III: Table of Contents Uniform Rules of Evidence with 2005 Amendments Table of Cases.
Klotter, John C. Criminal Evidence.7th ed. c2000
Keywords: Evidence, Criminal -- United States